2019
DOI: 10.1016/j.cortex.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Becoming aware of subliminal responses: An EEG/EMG study on partial error detection and correction in humans

Abstract: In experimental settings, most overt behavioral errors are consciously perceived. They are, however, only the tip of the iceberg, and electromyographic recording of the muscles involved in the response reveals subthreshold incorrect response activations. Although they are all efficiently corrected, such "partial errors" are poorly consciously detected. Electroencephalographic recordings (CSD estimate), revealed the sequence of cortical activities that lead, or not, to conscious detection. Besides medioprefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…This activation has been interpreted as due to sub-threshold responses (i.e., errors corrected ‘in flight’ or partial errors). Consistently, other studies conducted with different methods—including EMG and/or dynamometer [ 15 , 20 , 21 ]—have shown sub-threshold responses in similar and different cognitive domains.…”
Section: Introductionsupporting
confidence: 84%
“…This activation has been interpreted as due to sub-threshold responses (i.e., errors corrected ‘in flight’ or partial errors). Consistently, other studies conducted with different methods—including EMG and/or dynamometer [ 15 , 20 , 21 ]—have shown sub-threshold responses in similar and different cognitive domains.…”
Section: Introductionsupporting
confidence: 84%
“…This phenomenon indexes covert impulsive response activation and is known as a "partial error" to indicate that a potentially erroneous response was corrected before actual response execution. Hence, while EMG allows the expression of activation and suppression mechanisms to be measured at the peripheral level, it also provides information about brain perceptual gating phenomena (Servant, White, Montagnini, & Burle, 2016) and inhibitory control originating from frontal brain regions (Ficarella, Rochet, & Burle, 2019) . The rate of partial errors not only provides an index of the susceptibility to response capture, but their latencies can also be used to perform a more dynamic analysis of response activation.…”
Section: Introductionmentioning
confidence: 99%
“…In between-hand choice RTs tasks, Eriksen et al (1985) and Coles et al (1985) observed that correct responses were sometimes preceded by a small sub-threshold EMG activation (insufficient to trigger an overt response) on the ''wrong'' side. These results have often been reproduced ever since (e.g., Masaki and Segalowitz, 2004;Allain et al, 2009;Maruo et al, 2017;Ficarella et al, 2019). Given that these activities occur in the ''wrong'' effector, they have been considered to be partial errors (see Figure 3 for an illustration), and ''analysis of these partial errors reveals that things may be going wrong with the system, even when its final output, the overt behavioral response, is correct'' (Coles et al, 1995, p. 130).…”
Section: What Does a Human Do When He Is About To Make An Error?mentioning
confidence: 67%
“…Post-partial error slowing has also been evidenced (Allain et al, 2009), although it is much smaller than PES; however, it must be noticed that: (1) the delay separating partial error onset from the stimulus of the next trial is longer than that separating errors from the following stimulus and, as it has been indicated above, the longer this delay, the smaller PES; and (2) partial errors are separated from the next stimulus by the correct overt response, and it is noteworthy that Fiehler et al (2005) failed to evidence any PES following corrected overt errors. More recently, Ficarella et al (2019) added new insight regarding the nature of these sequential effects. Post (partial)error slowing occurs in a subset of partial errors only-the minority (about one third: Rochet et al, 2014) of the partial errors which are consciously detected.…”
Section: What Does a Human Do When He Is About To Make An Error?mentioning
confidence: 99%